Pengaruh e-service quality, live streaming shopping dan flash sale terhadap keputusan pembelian produk fashion pada platform Shopee - Ardila, Ardila; Saino, Saino (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
This research was conducted to analyze the effect of e-service quality, live streaming shopping, and flash sales on purchasing decisions for fashion products on the Shopee Platform. This research was conducted in Surabaya with a population of people who live in Surabaya and by the research boundaries set by the researcher, namely respondents at least 17 years old, Shopee users, and have purchased fashion products at least three times and have seen and purchased fashion products on Shopee live and Shopee flash sales. This research's primary data was obtained by distributing questionnaires to a research sample of 150 respondents. The quantitative method used in this study is the PLS-SEM (Partial Least Square- Structural Equation Modeling) data analysis technique. Based on the results of data analysis, it is found that e-service quality, live streaming shopping, and flash sales have a positive and significant effect on purchasing decisions for fashion products on the Shopee platform.